Aplicação de modelo de revisão periódica multiperíodo como política de planejamento de estoques no setor de peças primárias subcontratadas na indústria aeroespacial - Kernbichler, Tiago Sanches (2016)
This dissertation studies the application of a periodic review inventory model based on the multiperiod newsboy problem, as an effective alternative to reach a well balanced inventory planning policy of subcontractors primary parts area of the aerospace industry. In Brazil, the aerospace industry is responsible for a large amount of the country exports and this industry competes with other globally aerospace supply chains in a scenario increasingly turbulent and demanding for fast deliveries, with high quality levels and low cost. The purpose of this work is to study and propose this alternative for optimizing the inventory planning by means of a quantitative approach, applied in a primary parts sector of the aerospace industry, it will focus in a specific group of items with high annual demand value. The main objective of this approach is to balance the high inventory costs with a high service level demanded in this industry, and efficiently respond the stakeholders expectations, with superior performance of the usual models adopted by this industry, and give a better support to the decision makers in a tactical-operational level. The result obtained show the potential of the method to improve the performance of these inventory management and planning systems.